Steering the Electron in H+2 by Nuclear Wave Packet Dynamics - Fischer, Bettina; Kremer, Manuel; Pfeifer, Thomas; Feuerstein, Bernold; Sharma, Vandana; Thumm, Uwe; Schröter, Claus Dieter; Moshammer, Robert; Ullrich, Joachim (My University, 2010)
By combining carrier-envelope phase (CEP) stable light fields and the traditional method of optical pump-probe spectroscopy we study electron localization in dissociating H+2 molecular ions. Localization and localizability of electrons is observed to strongly depend on the time delay between the two CEP-stable laser pulses with a characteristic periodicity corresponding to the oscillating molecular wave packet. Variation of the pump-probe delay time allows us to uncover the underlying physical mechanism for electron localization, which are two distinct sets of interfering dissociation channels that exhibit specific temporal signatures in their asymmetry response.